2018
DOI: 10.3390/rs10050766
|View full text |Cite
|
Sign up to set email alerts
|

DMBLC: An Indirect Urban Impervious Surface Area Extraction Approach by Detecting and Masking Background Land Cover on Google Earth Image

Abstract: Implying the prosperity and development of the city, impervious surface area (ISA) is playing an increasingly important role in ecological processes, microclimate, material and energy flows, and urban flood. The free sub-meter resolution Google Earth image, which is integrated by several high spatial resolution data, appears to have potential for high-resolution ISA extraction, where present study is rare and performances remain to be improved. Due to the high spatial and spectral variation of the urban enviro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 50 publications
0
7
0
Order By: Relevance
“…Qualitative performance appraisals were adopted on the basis of this technique. The PA, UA, OA, and kappa coefficient (KC) values were calculated with a confusion matrix from the detected results, and the ground truth data were collected from different locations in the study area [22,59]. The PA is the error emission in the classified images, and the UA is the reliability; the probability of a pixel on the map represents that of the same category on the ground.…”
Section: Accuracy Assessment and Data Validationmentioning
confidence: 99%
See 1 more Smart Citation
“…Qualitative performance appraisals were adopted on the basis of this technique. The PA, UA, OA, and kappa coefficient (KC) values were calculated with a confusion matrix from the detected results, and the ground truth data were collected from different locations in the study area [22,59]. The PA is the error emission in the classified images, and the UA is the reliability; the probability of a pixel on the map represents that of the same category on the ground.…”
Section: Accuracy Assessment and Data Validationmentioning
confidence: 99%
“…The driving forces of unplanned impervious surface expansion are divided into two categories: potential and direct factors. Direct factors include development in terms of infrastructure, settlements, and industrial development, as mentioned by Lu et al and Huang et al [22,23]; and potential factors include technological, economic, population, policy, and natural factors [24][25][26]. Due to constraints in the availability of continuous statistical data, quantitative analyses are frequently used for impervious surface analyses [27].…”
Section: Introductionmentioning
confidence: 99%
“…8. This is because improved spatial resolution can minimize the mixed-pixel phenomenon and provide abundant information in the spatial domain, thus potentially increasing the accuracy and thematic details of IS mapping products (Huang et al, 2018). Moreover, the proposed framework was implemented on the GEE cloud platform, which provides almost all Sentinel-1/2 archive images across the entire time series and study area.…”
Section: Discussion 430mentioning
confidence: 99%
“…The use of Google Earth® platforms and SASPlanet® has been recurrent in several studies (Oliveira et al 2009;Schneider 2012;Hu et al 2013;Ghaffarian & Ghaffarian 2014;Jacobson et al 2015;Abdelaty 2016;Malarvizh, Kumar & Porchelvan 2016;Wibowo et al 2016;Huang et al 2018). In this sense, Hu et al (2013) revealed that no significant difference was found between these two classification results by adopting the Z Test, which strongly proved the potential of Google Earth® images in land cover and land use mapping.…”
Section: Introductionmentioning
confidence: 90%